2011
DOI: 10.1136/tobaccocontrol-2011-050171
|View full text |Cite
|
Sign up to set email alerts
|

Smokers' responses to television advertisements about the serious harms of tobacco use: pre-testing results from 10 low- to middle-income countries

Abstract: Television ads that graphically communicate the serious harms of tobacco use are likely to be effective with smokers in low- to middle-income countries and can be readily translated and adapted for local use. Ads with complex medical terms or metaphors, or those that feature personal testimonials, are more variable and at least require more careful pre-testing and adaptation to maximise their potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 25 publications
7
72
1
Order By: Relevance
“…However, the rating points likely do not explain all recollection, as the ad called "Emerging Man," which depicted a man popping out of a pizza oven and fish tank while talking about California laws, had the highest amount of rating points, but was among the least likely to be recalled. Given intended emotion, personal testimonial, and negative imagery depicted in "Stages," relative to "The Emerging Man", our results are consistent with other studies that indicate that advertisements depicting graphic images with personal narratives are more likely to be recalled (14,40,42,(48)(49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the rating points likely do not explain all recollection, as the ad called "Emerging Man," which depicted a man popping out of a pizza oven and fish tank while talking about California laws, had the highest amount of rating points, but was among the least likely to be recalled. Given intended emotion, personal testimonial, and negative imagery depicted in "Stages," relative to "The Emerging Man", our results are consistent with other studies that indicate that advertisements depicting graphic images with personal narratives are more likely to be recalled (14,40,42,(48)(49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 89%
“…Some evidence indicates that advertisements that use highly emotional imagery or rely on personal narratives may be recalled more often and confer greater effects on quitting behavior (12,14,26,27,29,33,(39)(40)(41)(42). Most of this evidence from population studies reliesy on aggregate measures of exposure to media (e.g.…”
Section: Despite This Current Weight Of Evidence and Recommendations mentioning
confidence: 99%
“…Tobacco tax increases can be used to fund key elements of comprehensive tobacco control programmes 48 and the cost of mass media campaigns can be minimized by adapting effective campaigns that have been used in other countries. 49 …”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wakefield et al (55), which covered 17 low-and middle-income countries, investigators tested five types of advertisements and found that three advertisements with graphic demonstrations performed consistently high across all countries. Two advertisements showed diseased body parts and one used a disgust-provoking metaphor to demonstrate tar accumulation in smokers' lungs.…”
Section: Media and Advertisingmentioning
confidence: 99%